Takotsubo cardiomyopathy (broken heart syndrome) - Doroteja Đekić; Anja Ćuk; Boško Skorić (Liječnički vjesnik, 2023)
Takotsubo cardiomyopathy (TC), also known as stress cardiomyopathy is an uncommon disease characterized by acute left ventricle (LV) failure that mimics acute coronary syndrome (ACS) but lacking evidence of obstructive coronary artery disease. It is usually precipitated by severe emotional or physical stress although its’ pathophysiology is not yet fully known. Most patients are women past the age of 50. In-hospital mortality is 3-4%.